The Indiana Learning Health System Initiative: Early experience developing a collaborative, regional learning health system. Issue 3 (23rd June 2021) - Schleyer, Titus; Williams, Linda; Gottlieb, Jonathan; Weaver, Christopher; Saysana, Michele; Azar, Jose; Sadowski, Josh; Frederick, Chris; Hui, Siu; Kara, Areeba; Ruppert, Laura; Zappone, Sarah; et al.
Abstract: Introduction: Learning health systems (LHSs) are usually created and maintained by single institutions or healthcare systems. The Indiana Learning Health System Initiative (ILHSI) is a new multi‐institutional, collaborative regional LHS initiative led by the Regenstrief Institute (RI) and developed in partnership with five additional organizations: two Indiana‐based health systems, two schools at Indiana University, and our state‐wide health information exchange. We report our experiences and lessons learned during the initial 2‐year phase of developing and implementing the ILHSI. Methods: The initial goals of the ILHSI were to instantiate the concept, establish partnerships, and perform LHS pilot projects to inform expansion. We established shared governance and technical capabilities, conducted a literature review‐based and regional environmental scan, and convened key stakeholders to iteratively identify focus areas, and select and implement six initial joint projects. Results: The ILHSI successfully collaborated with its partner organizations to establish a foundational governance structure, set goals and strategies, and prioritize projects and training activities. We developed and deployed strategies to effectively use health system and regional HIE infrastructure and minimize information silos, a frequent challenge for multi‐organizational LHSs. Successful projects were diverse and included deploying a Fast Healthcare Interoperability Standards (FHIR)‐based tool across emergency departments state‐wide, analyzing free‐text elements of cross‐hospital surveys, and developing models to provide clinical decision support based on clinical and social determinants of health. We also experienced organizational challenges, including changes in key leadership personnel and varying levels of engagement with health system partners, which impacted initial ILHSI efforts and structures. Reflecting on these early experiences, we identified lessons learned and next steps. Conclusions: Multi‐organizational LHSs can be challenging to develop but present the opportunity to leverage learning across multiple organizations and systems to benefit the general population. Attention to governance decisions, shared goal setting and monitoring, and careful selection of projects are important for early success.